Embedding free versus slave labor regulation in thetransatlantic British Empire and the United States, 1835-1860 / Incorporação livre versus trabalho escravo no regulamento transatlantico do Império Britânico e dos Estados Unidos, 1835-1860 - Freyer, Tony A. (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.16906 Trabalho enviado em 26 de abril de 2015. Aceito em 25 de maio de 2015 <p class="Paragraph SCX67842808" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Abstract <p class="Paragraph SCX67842808" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX67842808" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">This study problematizes the historical perspective of jurisdiction specific legal analysis by examining the international context of the development of national labor regulatory regimes in the United States and the United Kingdom during the transatlantic immigrant and antislavery crises in the mid-nineteenth century.2 This period is critical because of the desperate pressure these crises placed on large sources of labor at the bottom of society, poor immigrants and slaves. Starvation and enslavement compelled unprecedented migrations across national borders and within countries to different regions. The mobility of the populations brought them into contact with diverse forms of governance, from the regional differences within the balance of American federalism, to the competing national identities of the English, Irish and Canadian components of the British Empire. As a result, the transatlantic and intercontinental migrations are a particularly useful example for illustrating the importance of international context in the development of the law because of the different ways each governmental body responded to the social pressures. This study shows how the multiple and complex intergovernmental regulatory networks relating to the mobility of this labor force developed in an international context, not solely within the development of isolated national legal systems.3 <p class="Paragraph SCX67842808" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX67842808" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Keywords: Migration; jurisdiction, anti-slavery; international context; regulatory regimes; mobility Resumo Este estudo problematiza a perspectiva histórica da análise jurídica especificada jurisdição, examinando o contexto internacional do desenvolvimento nacional do trabalho de regimes reguladores nos Estados Unidos e no Reino Unido durante a imigração transatlântica e a crise abolicionista em meados do século XIX. Esse período é crítico devido à pressão desesperada que essas crises colocaram em grandes fontes de trabalho na base da hierarquia da sociedade, imigrantes pobres e escravos. A fome e a escravidão obrigaram migrações sem precedentes através das fronteiras nacionais e dentro dos países em diferentes regiões. A mobilidade das populações a pôs em contato com diversas formas de governança, a partir das diferenças regionais no equilíbrio do federalismo americano, para as concorrentes identidades nacionais dos ingleses, irlandeses e canadenses componentes do Império Britânico. Como resultado, as migrações transatlânticas e intercontinentais são um exemplo particularmente útil para ilustrar a importância do contexto internacional no desenvolvimento da lei por causa dos diferentes modos como cada órgão governamental respondeu às pressões sociais. Este estudo mostra como as múltiplas e complexas redes reguladoras intergovernamentais em matéria de mobilidade dessa força de trabalho se desenvolveram em um contexto internacional, não apenas no âmbito do desenvolvimento dos sistemas jurídicos nacionais isolados. Palavras-chave: Migrações; jurisdição; anti escravidão; contexto internacional; regimes reguladores; mobilidade